Strategic Approach: A Step towards Sustainable Solid Waste Management in Developing Economies - Jamwal, Divya Singh; Saurabh (Asian Journal of Empirical Research, 2019)
The present study is based upon the prevailing issue of Solid Waste Management (SWM) faced by developing economies all over the world. The quantum and composition of waste generation pose a series of complexities regarding surrounding institutions’ plans in dealing with it. In India, the responsibility of handling solid waste primarily falls to municipal authorities or Urban Local Bodies (ULBs). These ULBs are the main functional units that plan, implement and control the actions as well as resources used for SWM within their jurisdiction. This study explores a strategic approach of these ULBs towards the management of solid waste at the functional level across 10 districts in J&K, a state of India. The study advocates for the inclusion of strategic interventions in the field of SWM based on a survey conducted which establishes the gap in strategic implementation. The strategic approach in this study is related to understanding dimensions such as strategy formulation, implementation and evaluation that contributes to various aspects of SWM for theorists, policy makers and practitioners.